Practical Research of Electronic Transformer Based on Interpolation Algorithm - Li Zhenkun; Ji Hui; Fu Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
As a result of the adoption of new photovoltaic technology, electronic transformers have great advantages compared with traditional electromagnetic type, such as anti-saturated, high linearity, compact and lightweight etc. The working principle of sensing head of electronic current/voltage transformers is introduced in the paper. The causes of phase error in electronic transformer are analyzed. And a set of phase compensation methods based on the signal transfer principle of electronic transformer is presented. The phase-difference caused by Rogowski coil and time-delay in signal transferring from high voltage side to merging unit are analyzed, and the higher sampling rate and the method of linear interpolation is used to solve the problem. In the simulation test the phase error compensation effect is very good, and the simulation result shows that the integrated error after compensation is able to meet the requirements of the measurement and protection, and demonstrates the validity of the method. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1983